Physico-chemical and sensory qualities of Iberian sliced dry-cured loins from various commercial categories and the effects of the type of packaging and refrigeration time. (April 2021) - Contador, Rebeca; Ortiz, Alberto; Ramírez, María del Rosario; García-Torres, Susana; López-Parra, María Montaña; Tejerina, David
Abstract: The physico-chemical characteristics and sensory attributes of Iberian sliced dry-cured loin from three commercial categories according to the current Spanish Iberian Quality Standard ( Black, Red ; purebred Iberian and Iberian x Duroc-crossed (50%) pigs, respectively, reared outdoor with the final fattening phase based on acorns and grass; Montanera, and White ; Iberian x Duroc crossed (50%) pigs reared indoors and fed on commercial fodder) and packaged using different systems (vacuum and modified-atmosphere packaging, MAP) were evaluated at various stages throughout their long-term storage (12 months). The slices from the Black and Red categories yielded higher antioxidants, monounsaturated and polyunsaturated fatty acids and higher lipid oxidation at the end of storage time (from t8 to t12). α-tocopherol was better preserved in the case of the slices kept in MAP although, after 8 months of storage, lipid oxidation was seen to increase in the latter (Δt12-t0 MAP = 0.4) compared to the vacuum packaged product. Regarding sensory evaluation, the marbling and texture attributes were affected by commercial category, whereas the influence was insignificant by type of packaging and storage time. Highlights: Lipid oxidation throughout long-term storage depend on commercial category. Oxidative status was better preserved in vacuum with respect to MAP. Commercial category affects sensory attributes of dry-cured loin. Sensory attributes of dry-cured loin were not affected by packaging system.